Development of a Cost-Effective Twin-Disc Test Rig for Railway Wear Simulation - Siyasiya, Charles Witness; Leso, Tshenolo P.; Mostert, Roelf J.; Moema, Joseph (Applied mechanics and materials, 2024)
Maintenance due to the replacement of damaged wheels and rails due to rolling contact fatigue (RCF) and wear has been found to be the major problem to rail operating companies. This problem tends to lead to unavailability of railway networks. To solve this problem, costly wear simulators are developed to predict the wear behaviour of the rails and wheels to improve the preventive maintenance in pursuit of operational efficiency. Therefore, more studies that simulate a combination of rolling and sliding wear, together with RCF, are required, specifically for the Southern African, where good and cost-effective rail wear simulators are not readily available. The problem with wear and RCF simulators is high production costs, so this work aims to solve this problem by developing a cost-effective wear test rig that is capable of simulating RCF, sliding and rolling wear as experienced by the train wheel while moving along railway tracks. For this work, it was decided that twin-disc concept would be used, since literature clearly shown that the method was able to simulate the three damage mechanisms mentioned. The developed twin-disc wear simulator was able to simulate both rolling and sliding wear and parameters including contact load and slip ratio could be changed with ease so to simulate the actual contact conditions between the wheel and rail. Outputs such as coefficient of friction and wheel disc temperature were obtained. The results showed that the severity of wear is heavily dependent on slip ratio i.e., increased with slip ratio, with both coefficient of friction and wear rate increasing with slip ratio.